The verapamil transporter in human alveolar epithelial cells (A549) does not interact with β2-receptor agonists - EHRHARDT, CARSTEN (My University, 2014)
Affinity of different organs for verapamil is highly variable and organ-specific. For example, the drug exhibits high levels of accumulation in lung tissues. A transporter recognising verapamil as substrate has previously been identified in human retinal pigment epithelial (RPE) and in rat retinal capillary endothelial (TR-iBRB2) cells. This transporter is distinct from any of the cloned organic cation transporters. Therefore, we hypothesised that the verapamil transporter is also functionally expressed in the human respiratory mucosa. Moreover, we tested the hypothesis that this transporter interacts with pulmonary administered cationic drugs such as ?2-agonists. The uptake of [3H]-verapamil was studied in A549 human alveolar epithelial cell monolayers at different times and concentrations. The influence of extracellular proton concentration and various organic cations on verapamil uptake was determined. Verapamil uptake into A549 cells was time- and concentration-dependent, sensitive to pH and had a Km value of 39.8 ? 8.2 ?M. Verapamil uptake was also sensitive to inhibition by amantadine, quinidine and pyrilamine, but insensitive to other typical modulators of organic cation and choline transporters. Whilst we demonstrated functional activity of the elusive verapamil transporter at the lung epithelium, our data suggest that this transporter does not interact with ?2-agonists at therapeutic concentrations.
PUBLISHED
Keywords: Organic cation transporters; Immunology, Inflammation & Infection